Diffuse alveolar hemorrhage caused by exposure to organic dust. (2015) - Suzuki, Yuzo; Imokawa, Shiro; Nihashi, Fumiya; Uto, Tomohiro; Sato, Jun; Suda, Takafumi
Abstract: Diffuse alveolar hemorrhage, a life-threatening disease, can complicate various conditions. We herein describe, for the first time, a patient with diffuse alveolar hemorrhage caused by exposure to organic dust. A 49-year-old woman who worked as a cantaloupe farmer in a greenhouse was referred to our hospital for sudden onset of dyspnea 3 h after exposure to organic dust. A chest X-ray and computed tomography scan performed on admission showed diffuse ground-glass opacities in both lung fields. Suspecting hypersensitivity pneumonitis, fiberoptic bronchoscopy was performed. Mucopurulent sputum was present in the trachea and both bronchi, and bronchoalveolar lavage revealed a progressively bloody return, typical of diffuse alveolar hemorrhage. Based on the history and bronchoscopy findings, she was diagnosed with diffuse alveolar hemorrhage following exposure to organic dust and was treated with antibiotics and corticosteroids. Diffuse alveolar hemorrhage should be considered in the differential diagnosis of diffuse ground-glass opacities observed on radiographs in farmers following exposure to organic dust.